Amitriptyline potently neutralizes distinct SARS-CoV-2 variants including D614G, Omicron BA.5, and Omicron XBB.1 - Zydek, Isabel; Thümmler, Laura; Beckmann, Nadine; Sehl, Carolin; Soddemann, Matthias; Grüneberg, Rabea; Elsner, Carina; Kamler, Markus; Dittmer, Ulf; Witzke, Oliver; Kadow, Stephanie; Gulbins, Erich; et al. (Frontiers in Microbiology, 2025)
IntroductionCOVID-19, caused by SARS-CoV-2, remains a global health challenge despite the availability of vaccines and antiviral treatments. The emergence of immune escape variants and the persistence of long COVID symptoms continue to complicate prevention and therapy, especially in low-resource settings. Functional inhibitors of acid sphingomyelinase (FIASMAs) have shown promise as broad-spectrum antiviral agents.MethodsWe evaluated the antiviral efficacy of amitriptyline, a widely used antidepressant and known FIASMA, against SARS-CoV-2. In vitro neutralization assays using pseudotyped virus-like particles (VLPs) and clinical isolates were performed to assess its ability to inhibit viral entry and replication.ResultsAmitriptyline significantly inhibited infection by SARS-CoV-2 VLPs bearing spike proteins, including those with mutations in the receptor-binding domain. Moreover, it reduced replication of clinical SARS-CoV-2 isolates D614G, Omicron BA.5, and Omicron XBB.1 in a dose-dependent manner at subtoxic concentrations.DiscussionOur findings demonstrate that amitriptyline neutralizes SARS-CoV-2 across multiple variants. These results support the potential of amitriptyline as a repurposed antiviral drug. Further clinical studies are warranted to evaluate its efficacy and safety in treating COVID-19 in humans.